Pengaruh Teknik Massage Punggung terhadap Intensitas Nyeri pada Ibu Bersalin Primigravida Fase Aktif Kala 1 di Masa Pandemi Covid-19 dan New Normal - Haryati Astuti (Neolectura, 2022)
The COVID-19 outbreak, which hit us at this time, where 62.7% of deliveries were assisted by midwives, so that midwives are expected to be able to provide good service while protecting themselves from contracting the COVID-19 virus, which greatly impacts psychological problems. First stage labor pain is a very worrying problem for inpartu mothers, especially primigravida mothers, and usually the most often done to reduce pain is the massage method. This study aims to determine the effect of back massage techniques on pain intensity in primigravida mothers in active phase 1 during the COVID-19 pandemic and the new normal. The results of the intervention with 15 pretest respondents (mother giving birth before back massage) quantitative design with Quasy Experiments one group pretest-posttest from 15 respondents found 3 respondents mild pain (20.%), 7 respondents moderate pain (70.2%) and 5 respondents experienced severe pain (9.8%), while the results of the post test (mother giving birth after a back massage) of 15 respondents found 2 respondents had mild pain (15%), 12 respondents had moderate pain (80%) and 1 respondent experienced severe pain (5%) ). And the results of the bivariate analysis of the average difference in the effect of before and after back massage techniques on pain intensity in primigravida mothers in active phase 1 with p 0.000. Of the 15 respondents from the rapid test results, 3 inpartu mothers were reactive for COVID-19 and isolated but still under observation according to the guidelines for the management of mothers in labor with COVID-19.